Turnaround Time Efficiency In MRO Industry : A DMAIC Based Evaluation Of Gate System Quality Performance at PT. GMF AeroAsia - Labiiba, Luthfi Rofif; Mulyono Azis, Anton (ADPEBI Publisher, 2026)
This research was conducted to evaluate the implementation of gate-based quality control in the engine maintenance process to improve turnaround time (TAT) efficiency in the maintenance process. TAT is a key indicator for assessing operational efficiency in the maintenance, repair, and overhaul (MRO) industry and affects customer satisfaction levels. Based on the operational data of PT. GMF AeroAsia for the period 2022-2024, TAT often does not meet the targets set in the service level agreement (SLA). One of the causes is the delay that occurs at gate 4-5 in the gate system. The research conducted used Six Sigma DMAIC to evaluate and identify the root causes of issues occurring in the maintenance process, as well as to examine the influence of factors such as working capital, external vendor causes, and material procurement related to the delays at gate 4-5. The method used in this research employs both quantitative and qualitative approaches by collecting data through historical data, observations, and interviews. The research results indicate that the implementation of Six Sigma DMAIC at gates 4-5 is not yet optimal, with delays predominantly caused by working capital and external vendor issues. This study found a strong correlation between the frequency of delays and the duration of delays with the total TAT. These findings suggest that the integration of Six Sigma DMAIC, supported by Critical Chain Project Management and Reliability Centered Maintenance, could be a solution to improve the efficiency occurring in the gate 4-5, thereby directly enhancing the TAT efficiency.